Effect of Different Concentrations in Yeast Biomass on the Seed Germination of Black Gram and Green gram - Subasri, J (International Journal of Pharmaceutical & Biological Archive, 2012)
Effect of Different Concentrations in Yeast Biomass on the Seed Germination of Black Gram and Green gram